Regional Data Mining Implementation Of Contraceptive Equipment Users In The City Of Binjai By Type Using Clustering method - Edelwais, Nurul; Simanjuntak, Magdalena; Sihombing, Marto (Yayasan Kita Menulis, 2023)
The government of the Binjai City BKKBN Office is one of the institutions responsible for controlling population growth and family planning in Indonesia which has a long-term impact that will occur if the family planning program is not implemented properly, there will be a population explosion and will cause various problems, including declining degree of health, social welfare, economic and cultural issues. Therefore, it is important to understand about contraception which will be useful in assisting the community in regulating birth rates and improving the quality of life, how contraceptives are used in Binjai City and how the levels of their use vary by region. This study aims to identify areas that use contraceptives in Binjai City based on the type of contraceptive used and to provide useful information for the government and health organizations in making policies and programs that benefit the community. Based on the results of the research conducted using a sample of 20 data, the results obtained from the data group are 12 data with the area group of contraceptive users in Binjai City based on their type with Age (X) being 18-25 years, and for the Kelurahan group (Y) is Binjai , and the type of contraception (Z ) injection for family planning.